Interacting Effects of Self-reported Physical Activity and Protein Preloads on fNIRS Measured Brain Activation During Ice Cream Intake (P08-012-19). (24th October 2019) - Lanza, Lisa; Albajri, Eram; Ayaz, Hasan; Smith, Sinclair; Parigi, Angelo Del; Nasser, Jennifer
Abstract: Objectives: To assess the effect of two preloads varying in protein, and self-reported physical activity (PA) on intake and brain activation (medial prefrontal cortex, mPFC) during eating of ice cream using functional near-infra red spectroscopy (fNIRS). Methods: Twenty-eight participants (15 m, 13 f) attended two randomly assigned sessions, consuming either a high (HP, 28 grams) or low protein (LP, 2 grams) equicaloric 120 kcal preload. After 15 minutes, the fNIRS sensor was fitted and a 2 minutes "baseline" of viewing nature scene pictures was recorded. Participants were then presented with a bowl of vanilla ice cream and allowed to eat ad libitum for ten minutes. fNIRS scan data was denoised using a low pass time filter of 30 seconds, and then peak height for mPFC was analyzed. Participants recorded their habitual PA using the Rubenstein-Mortenson Short PA Questionnaire (PAQ-M 2011). After a frequency analysis of questionnaire total scores, the sample was divided into two groups based on a median split (those reporting less than 134 minutes of PA/week and those reporting 134 or greater minutes of PA/week. Results: After controlling for BMI, the amount of ice cream consumed and total eating time observed under the LP condition differed significantly between the two groups (F = 14.8, P < 0.01, F = 4.3, P = 0.025, respectively). There was no significant difference in intake or total eating time between the LP and HP conditions. Peak mPFC activity and time to peak activity did not differ significantly between the groups under either preload condition, most likely due to small sample size. Conclusions: Results suggest that engaging in habitual PA of at least 134 minutes/week promotes consumption of fewer kcal of a high sugar/fat low protein food in an eating episode, most likely due to reduction in length of the eating episode. High protein preload content did not further reduce food intake over that due to physical activity. Increasing sample size is needed to determine the effect of habitual exercise on peak mPFC activity and time to peak activity. Funding Sources: Supported by a Seed Grant from the College of Nursing and Health Professions, Drexel University.